The internal situation of Kamianets-Podilskyi in the summer of 1648 in the correspondence of Łukasz Miaskowski, the Podolia district judge - Śliwińska-Słomska, Izabela (City and War, 2021)
Łukasz Miaskowski, a Podolia District Judge and Marshal of the Podolia Hood Court during the interregnum after the death of Władysław IV, was in the summer of 1648 in Kamianets- -Podilskyi. Due to his extensive contacts with the elite of the Principality of Moldavia, he obtained, aggregated and passed on to the elites of the Polish- Lithuanian Commonwealth information about events that took place in the Danubian principalities, the movements of the Tatar troops or the internal situation in the Ottoman Empire. In the summer of 1648, in the first period of Khmelnytsky’s Uprising, he also reported on the progress in the offensive of the Cossack troops, the mood among the rural population of Podolia and the Ukrainian lands, and the internal situation of Kamianets- -Podilskyi. The analysis of the sources included in the article shows the technical condition of the fortress, the number of its crew and factors impacting the morale of its defenders, such as: fear of attack by the Cossacks and Tatars and fear of betrayal by the Ruthenians staying in the city. The addressees of Miaskowski’s correspondence include Grand Chancellor of the Crown Jerzy Ossoliński, Grand Standard-Bearer of the Crown Aleksander Koniecpolski, Crown Field Clerk Adam Hieronim Sieniawski or Lviv Chamberlain, and privately the sender’s brother, Wojciech Miaskowski.